Covalent Mixing in the 2D Ferromagnet CrSiTe3 Evidenced by Magnetic X‐Ray Circular Dichroism. Issue 4 (30th December 2021) - Achinuq, Barat; Fujita, Ryuji; Xia, Wei; Guo, Yanfeng; Bencok, Peter; van der Laan, Gerrit; Hesjedal, Thorsten
Abstract : The low‐temperature electronic structure of the van der Waals ferromagnet CrSiTe 3 is investigated. This ferromagnetic semiconductor has a magnetic bulk transition temperature of 33 K, which can reach up to 80 K in single‐ and few‐layer flakes. X‐ray absorption spectroscopy (XAS) and X‐ray magnetic circular dichroism (XMCD) measurements, carried out at the Cr L 2, 3 and Te M 5 edges in vacuo‐cleaved single crystals, give strong evidence for hybridization‐mediated superexchange between the Cr atoms. The observed chemical shift in the XAS, as well as the comparison of XMCD with the calculated Cr L 2, 3 multiplet spectra, confirms a strong covalent bond between the Cr 3 d ( e g ) and Te 5 p states. Application of the XMCD sum rules gives a nonvanishing orbital moment, supporting a partial occupation of the e g states, apart from t 2 g . Also, the presence of a nonzero XMCD signal at the Te M 5 edge confirms a Te 5 p spin polarization due to mixing with the Cr e g bonding states. The results strongly suggest that superexchange, instead of the previously suggested single‐ion anisotropy, is responsible for the low‐temperature ferromagnetic ordering of 2D materials such as CrSiTe 3 and CrGeTe 3 . This demonstrates the interplay between electron correlation and ferromagnetism in insulating 2D materials. Abstract : The 2D van der Waals ferromagnet CrSiTe 3 is unique in that the magnetic transition temperature increases as the system gets thinner, reaching the mono‐ and few‐layer limit. Understanding this unique behavior, not observed in related 2D materials such as CrGeTe 3, provides a key to engineering high‐temperature monolayer ferromagnetic van der Waals materials. Achinuq et al. made a major step in this direction by unraveling the strong covalent bond between Te 5 p and Cr 3 d ( e g ) states.